Allometric models for estimating volume and total aboveground biomass of seven dominant tree species in a tropical humid forest in Costa Rica - Segura, O.; Kanninen, M. (2005)
Allometric equations for the estimation of tree volume and aboveground biomass in a tropical humid forest were developed based on direct measurements of 19 individuals of seven tree species in Northern Costa Rica. The volume and the biomass of the stems represented about two-thirds of the total volume and total aboveground biomass, respectively. The average stem volume varied between 4 and 11 Mg/tree and the average total aboveground biomass ranged from 4 to 10 mg/tree. The mean specific gravity of the sampled trees was 0.62 ± 0.06 (g/cm3). The average biomass expansion factor was 1.6 ± 0.2. The best-fit equations for stem and total volume were of logarithmic form, with diameter at breast height (R2 = 0.66 - 0.81) as an independent variable. The best-fit equations for total aboveground biomass that were based on combinations of diameter at breast height, and total and commercial height as independent variables had R2 values between 0.77 and 0.87. Models recommended for estimating total aboveground biomass are based on diameter at breast height, because the simplicity of these models is advantageous. This variable is easy to measure accurately in the field and is the most common variable recorded in forest inventories. Two widely used models in literature tend to underestimate aboveground biomass in large trees. In contrast, the models developed in this study accurately estimate the total aboveground biomass in these trees.